2013
DOI: 10.1017/s1366728912000739
|View full text |Cite
|
Sign up to set email alerts
|

Gender inferences: Grammatical features and their impact on the representation of gender in bilinguals

Abstract: We investigated the effects of grammatical and stereotypical gender information on the comprehension of human referent role nouns among bilinguals of a grammatical (French) and a natural gender language (English). In a sentence evaluation paradigm, participants judged the acceptability of a gender-specific sentence referring to either a group of women or men following a sentence containing the plural form of a role noun female (e.g., social workers), male (e.g., surgeons) or neutral (e.g., musicians) in ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 69 publications
(103 reference statements)
1
27
0
1
Order By: Relevance
“…Such findings suggest that new L2 grammatical forms that have or lack specific gender associations may be acquired in parallel with one's native language, to the point that they may affect readers' gender representations. These findings concur with those of Sato et al (2013) who reported that bilinguals may alter their representational tendencies in function of the languages shifts they undergo during reading processes.…”
Section: Discussionsupporting
confidence: 92%
“…Such findings suggest that new L2 grammatical forms that have or lack specific gender associations may be acquired in parallel with one's native language, to the point that they may affect readers' gender representations. These findings concur with those of Sato et al (2013) who reported that bilinguals may alter their representational tendencies in function of the languages shifts they undergo during reading processes.…”
Section: Discussionsupporting
confidence: 92%
“…It is a robust generalization from psycholinguistic studies that, at least when minimal context is provided, masculine g-gender most often triggers reference to socially male individuals. This has been shown through a variety of association tasks (Brauer and Landry, 2008;Chatard et al, 2005;Gygax et al, 2012), possible continuation tasks (Gygax et al, 2008;Sato et al, 2013), eye tracking experiments (Irmen and Schumann, 2011), and can also be seen in the interpretation of neologisms (Bonami and Boyé, 2017). 32 So a theory of the meaning of g-gender marking must take into account the existence of a relationship between masculine g-gender and male social gender and feminine grammatical gender and female social gender.…”
Section: Grammatical Gender and Social Meaningmentioning
confidence: 89%
“…More specifically, we explicitly asked participants, for each narrative, to decide, as fast as possible, whether the target sentence was a sensible continuation of the preceding narrative. This task has been used in a number of experiments interested in mapping processes of particular information to its antecedent context (e.g., Tanenhaus & Carlson, 1990, on anaphoric resolution; Reynolds, 2012, andSato, Gygax, &Gabriel, 2013, on gender inferences). In this task, response latencies are particularly important and informative, as they precisely signal (i.e., more precisely than reading times according to Tanenhaus & Carlson, 1990) the ease in which certain textual elements can be mapped onto readers' mental representation of the text.…”
Section: Methodsmentioning
confidence: 99%